Effects of the incoherent pumping in the linear optical susceptibility of an spherical nanostructure (2022)
The effects of incoherent exciton pumping on a semiconductor nanostructure with spherical geometry that interacts with monochromatic light are studied. The dissipative processes of spontaneous emission and dephasing were considered through the formalism of open quantum systems, using a master equation with Lindblad terms, where incoherent pumping is also included. The perturbative expansion technique was used on the density operator applied on the polarization operator. An expression of linear optical sus- ceptibility was obtained in a nanostructure that includes incoherent pumping. In addition, it was found that the incoherent pumping of excitons does not affect the energetic separation of the levels of the quantum system.